Effects of Hydrothermal Pretreatment and Hydrochar Addition on the Performance of Pig Carcass Anaerobic Digestion - Xu, Jie; Lin, Hongjian; Sheng, Kuichuan (Frontiers in Microbiology, 2021)
Proper disposal and utilization of dead pig carcasses are problems of public concern. The combination of hydrothermal pretreatment (HTP) and anaerobic digestion is a promising method to treat these wastes, provided that digestion inhibition is reduced. For this reason, the present research studied the effect of HTP temperature on biodegradation of organic components present in pork residues, as well as the effect of hydrochar addition on biogas yield after HTP of pork products. According to our results, 90% of lipids and 10% of proteins present in the pork were decomposed by HTP. In addition, after a HTP of 170°C, COD in liquid products (LP) reached 192.6 g/L. The biogas production from the solid residue (SR) and LP was up to 478 mL/g-VS and 398 mL/g-COD, respectively, when digestion was performed on a batch reactor. The inhibition of biogas generation due to excess of ammonia was reduced by the addition of hydrochar to the CSTR during co-digestion of SR and LP. After adding 6 g/L hydrochar to the reactor, maximum ammonia concentration tolerated by methanogens increased from 2.68 g/L to 3.38 g/L. This improved total biogas yield and degradation rate of substrates, reaching values of 28.62% and 36.06%, respectively. We propose that acetate content in VFA may be used as an index that reflects the degree of methanogenesis of the system. The results of the present work may also provide guidance for the digestion of feedstock with high protein and lipid content.